2007
DOI: 10.1097/01.anc.0000267913.58726.f3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Cost of the Moderately Preterm Infant

Abstract: Although morbidities with long-term consequences were rare, there is a significant burden on the infant, family, and healthcare team for patients 32 to 34 weeks' GA. It is important to understand the characteristics of this group of infants and explore ways of optimizing care to minimize this burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 16 publications
1
51
2
5
Order By: Relevance
“…The cost of managing ELBW infants varies between developed and developing countries and different regions within a country 4,6,15,16 17 . In the South African study 14 , mean duration of mechanical ventilation was 8.08 days and the mean duration of supplemental oxygen was 8.2 days in VLBW babies.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of managing ELBW infants varies between developed and developing countries and different regions within a country 4,6,15,16 17 . In the South African study 14 , mean duration of mechanical ventilation was 8.08 days and the mean duration of supplemental oxygen was 8.2 days in VLBW babies.…”
Section: Discussionmentioning
confidence: 99%
“…The original DIVA score defined history of prematurity as patients born at less than 38 weeks' gestational age, thus giving patients born at 37 weeks and 6 days the same score as those patients born at 24 weeks of gestation. The impetus for gathering NICU LOS data was the belief that there is a difference between extreme preterm and near-term infants 5,6 and that these differences may contribute to difficulty with venous cannulation. Ultimately, NICU LOS was transformed to history of NICU admission, yes or no due to paucity of children in this study who were born premature.…”
Section: Methodsmentioning
confidence: 99%
“…2- 4 The increased risk of adverse sequelae following LMPT birth is likely to translate into economic consequences for health services and other sectors of the economy, 5 the study of which has been highlighted as a priority area for research enquiry. 6 A recent structured review summarising published evidence on the economic consequences of LMPT birth, 6 found that ten studies, published between 1980 and 2011, focused on economic costs during the infant's initial hospitalisation, [7][8][9][10][11][12][13][14][15][16] whereas 13 studies reported economic costs in some form following the infant's initial hospitalisation.…”
Section: Introductionmentioning
confidence: 99%